Preliminares sobre virus infectando banano en el noroeste de Argentina - Cabrera Mederos, Dariel; Nome Docampo, Claudia; Jaramillo, M.; Ortiz, Claudio Manuel; Flores, Ceferino Rene; Trucco, Veronica Milagros; Castellanos Collazo, Onias; Portal, O.; Giolitti, Fabian (Asociación Argentina de Fitopatólogos, 2021)
Poster